2001
DOI: 10.1002/ana.1287.abs
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral nervous system infection, immunity, and inflammation in the nonhuman primate model of lyme borreliosis

Abstract: The relationship between chronic infection, antispirochetal immunity, and inflammation is unknown in Lyme neuroborreliosis. In the nonhuman primate model of Lyme neuroborreliosis, we measured spirochetal density in the nervous system and other tissues by polymerase chain reaction and correlated these values to anti-Borrelia burgdorferi antibody in the serum and cerebrospinal fluid, and to inflammation in tissues. Despite substantial presence of Borrelia burgdorferi, the causative agent of Lyme borreliosis, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…During infections of immunosuppressed NHPs inoculated by syringe with N40, we found that skeletal muscles had the highest spirochetal load of all the tissues examined (11). During infections of transiently immunosuppressed (TISP) NHPs, we found that skeletal and cardiac muscles had the most severe inflammation of all the tissues examined (40).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…During infections of immunosuppressed NHPs inoculated by syringe with N40, we found that skeletal muscles had the highest spirochetal load of all the tissues examined (11). During infections of transiently immunosuppressed (TISP) NHPs, we found that skeletal and cardiac muscles had the most severe inflammation of all the tissues examined (40).…”
mentioning
confidence: 81%
“…strains were used for inoculation. B. burgdorferi sensu stricto strain N40 was used in previous studies with the NHP model of Lyme disease (40)(41)(42). For the first time, some NHPs were inoculated with strain N40 by tick bite rather than by needle.…”
Section: Methodsmentioning
confidence: 99%
“…5 The immunoblot for all inoculated NHPs have been reported. 5,16,17 Table 1 also summarizes the immunoblot results for the BbN40-inoculated immunocompetent NHPs: all that were tested had positive Lyme IgG WB at necropsy and none had positive IgM WB when examined later than 6 months after inoculation. All WB from garinii-inoculated NHPs were negative even when tested with homologous sonicates, 5 an indication that NHPs are resistant to syringe inoculation of garinii strains of Lyme disease borrelias.…”
Section: Antibody Responsementioning
confidence: 99%
“…Commercial B. burgdorferi sensu stricto nitrocellulose strips (Microbiology Reference Laboratory, Cypress, CA, USA) were used as previously described 10,14 according to the instructions of the diagnostic kit. The strain used for preparation of these blots was a B. burgdorferi sensu stricto strain CB, an isolate from an erythema migrans lesion from a patient from Valhalla, NY.…”
Section: Immunoblottingmentioning
confidence: 99%
“…13 Both inflammation and infection are more prominent in the periphery than in the CNS. 13,14 The preferred localization in the spinal cord were the leptomeninges, nerve roots, and dorsal root ganglia. 13 For the present study, we focused on the spinal cord.…”
mentioning
confidence: 99%